Peran Manajemen Kurikulum Berbasis Industri Dalam Keterserapan Lulusan SMK Pelayaran Muhammadiyah Tuban - Erna Srifidias Titik; Taufiq Harris; A. Faizin . (CV. ITTC INDONESIA, 2026)
Vocational education plays a strategic role in preparing graduates who are ready to enter the workforce. However, the low employment absorption rate of Vocational High School (SMK) graduates indicates a mismatch between graduates’ competencies and the needs of Industry and the World of Work (IWW). This study aims to describe in depth: (1) the role of industry-based curriculum management in improving graduate employment absorption at SMK Pelayaran Muhammadiyah Tuban, (2) the challenges and efforts encountered in the implementation of industry-based curriculum management, and (3) its impact on vocational competencies and graduates’ work readiness. This study employed a descriptive qualitative approach with a case study strategy. Data were collected through in-depth interviews, participant observation, and documentation studies. The research subjects included the principal, vice principal for curriculum affairs, heads of expertise programs, productive subject teachers, industry partner representatives, and twelfth-grade students. Data analysis followed the Miles and Huberman model through data reduction, data display, and conclusion drawing/verification, supported by source and technique triangulation. The findings indicate that industry-based curriculum management at SMK Pelayaran Muhammadiyah Tuban is implemented through curriculum planning involving industry partners, the organization of learning aligned with industry needs, the implementation of learning that emphasizes real work practices through teaching factories and Industrial Work Practice (PKL), and continuous curriculum evaluation in collaboration with industry partners. The implementation of industry-based curriculum management has a positive impact on improving vocational competencies, work readiness, and graduates’ employment absorption in the industrial sector.